Atomic dynamics of alumina melt: A molecular dynamics simulation study - Jahn, S.; Madden, P.A. (Condensed Matter Physics, 2008)
The atomic dynamics of Al₂O₃ melt are studied by molecular dynamics simulation. The particle interactions are described by an advanced ionic interaction model that includes polarization effects and ionic shape deformations. The model has been shown to reproduce accurately the static structure factors S(Q) from neutron and x-ray diffraction and the dynamic structure factor S(Q, ω) from inelastic x-ray scattering. Analysis of the partial dynamic structure factors shows inelastic features in the spectra up to momentum transfers, Q, close to the principal peaks of partial static structure factors. The broadening of the Brillouin line widths is discussed in terms of a frequency dependent viscosity η(ω).